(untitled) (Herald of Journalism, 2019)
An important phase was reached by Kazakhstani journalism sector with the country’s independence. First of all, it achieved a more leveled ialogue with world-class journalism through the global Internet system. Some of the opinions implanted in the consciousness that took place during the oviet period have lost their meaning.Democratic features of foreign journalism, which have been negatively related for many years, have found their place in Kazakhstani journalism. Journalism based on human rights, freedom of speech, freedom of the press and diversity, has had a marked improvement in the political, social, economic and spiritual spheres of the country’s life. Journalism related to the political sphere has become viable as an important and very influential part of journalism, which covers all aspects of politics and political science both in state and non-governmental media. Since journalism needs more participation in all current problems of its existence, all media consist of genres and styles that consist of various topics. Publications and programs, even individual materials and presentations, are sometimes focused on all audiences, and sometimes on certain social and political groups (by profession, profession, interests, age, sex, etc.).